Behavioral Financial Analysis in Internal Locus of Control Mediation on Private Employees Surabaya - Lelli Kisdayanti; Tri Kartika Pertiwi (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
THIS RESEARCH aims to analyze the effect of financial knowledge, financial experience, and income on financial behavior through the internal locus of control of employees in Surabaya. The method used to determine the sample was purposive sampling and accidental sampling—the model used in this research area 100 respondents of employees in Surabaya. The data analysis technique used is the SmartPLS 3.0 software analysis. The research results that financial knowledge has a significant positive effect on the financial behavior of employees in Surabaya. Financial experience and income do not have a significant positive effect on the financial behavior of employees in Surabaya. Analysis of indirect variables using SEM PLS shows that locus of control internal can mediate financial knowledge and income on the financial behavior of employees in Surabaya. Meanwhile, the internal locus of power does not mediate financial experience on the financial behavior of employees in Surabaya.